Consumers’ willingness to pay for basic goods and services before and during pandemic Covid-19 in Malaysia - Md Jusoh, Zuroni; Zainudin, Norzalina; Paim, Laily; Ahmat, Nizam (Human Resource Management Academic Research Society, 2021)
In the early of 2020, Malaysia had been affected by the outbreak of Coronavirus Disease 2019 (COVID-19). With regards to what people are buying, Malaysians reported that they spend more on items with longer shelf life than they would usually do. The aim of this study to analyse the consumers’ willingness to pay (WTP) for goods and services before and during pandemic COVID-19. A total of 481 respondents involved in this study through convenience sampling method via self-administered questionnaires were distributed. Collected data were then analysed using Statistical Package for Social Sciences (SPSS) version 22 and EViews version 10. The mean WTP that consumers willing to pay for face mask was MYR1.92 (21.9%) during COVID-19 as compared before COVID-19 at MYR1.50. Meanwhile, Logit estimation result shows all of the predictor variables (ScoreDif, Age, Income1, Income2, Location and Family size) of WTP for higher prices were significant. In conclusion, the consumers were WTP more for basic goods and services during COVID-19 outbreak as compared before COVID-19 outbreak. Through this study, Malaysian consumers could get to know more about how much they are WTP for basic goods and services before and during COVID-19 outbreak.